The impact of teachers' pedagogical content knowledge in the teaching of "capacitance" to grade 11 physical sciences learners in Mpumalanga, South Africa. - Nkuna, Bailey Haizane (My University, 2013)
There has been poor performance of learners doing Physical Sciences in Mpumalanga in the past 6 years. This was evident on the exam statistics provided by the National department of education. (DoBE, 2012). The statistics show that learners from previously disadvantaged schools obtained an average performance of between 20% and 40% in their end of year results. The topic on “Capacitance” was previously taught to first year university students but has now been included to grade 11 and grade 12 syllabi as a new topic. The teachers’ ability to construct effective lessons on “Capacitance” has been blamed by both circuit managers and subject advisors for Physical Sciences. This study has investigated the impact of teachers’ Pedagogical Content Knowledge (PCK) in teaching the topic on “Capacitance”. The investigation focused on the teaching strategies that teachers use to help learners address learning problems in Physical Sciences, in the topic on “Capacitance”. The choice of this topic followed an interview conducted with two teachers attached to a teacher development programme. “Capacitance” is one of the new topics in which learners performed poorly. The research was guided by the following two research questions: 1. How is the teachers’ pedagogical knowledge (PCK) portrayed in teaching Capacitance? 2. To what extent have teachers’ mastered the Content Knowledge about Capacitance? A case study involving two grade 11 Physical Sciences teachers was utilized to gain the understanding of the teaching strategies. Data was collected through interviews and classroom observations. The data was analyzed by first discussing the two teachers’ depth of PCK during their teaching of the lessons on “Capacitance”. The data analysis also focused on the two teachers’ integration of Content Knowledge (CK) in their teaching. In addition, the data analysis enquired the teachers’ extent of content mastery. This was achieved by discussing the teachers’ Subject Matter Knowledge (SMK) and curricular saliency based on the observed lessons and recorded interviews.